Legal Protection For Abortion For People With Mental Disorders Who Are Pregnant With Children Resulting From Rape: Legal Protection For Abortion For People With Mental Disorders Who Are Pregnant With Children Resulting From Rape - Harung, Maria; Wiwik Afifah (International Conference of Innovation and Community Engagement, 2024)
This study focuses on the legal protection surrounding abortion for individuals with mental disorders who are pregnant as a result of rape. Abortions performed by vulnerable groups, such as people with mental disorders (ODGJ), are critical issues within the realms of law and reproductive health. Abortion is strictly regulated with specific conditions and exceptions, especially in cases involving victims of rape and life-threatening medical conditions. ODGJ represents a vulnerable group with limitations in making independent and legally valid medical decisions. This research utilizes a normative juridical method with legislative and conceptual approaches. The study’s findings indicate that abortion is permitted under certain conditions that meet medical and legal requirements, particularly in cases of pregnancy resulting from rape or life-threatening conditions for the mother. The Reproductive Health Law (Law Number 17 of 2023) grants women the right to choose abortion under specific circumstances, considering both physical and mental safety. Forms of protection for ODGJ undergoing abortion include access to comprehensive reproductive health services, legal assistance, and the guarantee of medical decisions supported by family or guardian consent. This protection also encompasses policies ensuring that the abortion process respects the rights and limitations of individuals with mental disorders and provides safe access to competent medical facilities.